Thermodynamics of a hyperthermostable carboxylesterase from Anoxybacillus geothermalis D9 - Mohd Johan, Ummie Umaiera; Raja Abd. Rahman, Raja Noor Zaliha; Ahmad Kamarudin, Nor Hafizah; Mohamad Ali, Mohd Shukuri (Elsevier, 2024)
Hyperthermostable enzymes are highly desirable biocatalysts due to their exceptional stability at extreme temperatures. Recently, a hyperthermostable carboxylesterase EstD9 from Anoxybacillus geothermalis D9 was biochemically characterized. The enzyme exhibited remarkable stability at high temperature. In this study, we attempted to probe the conformational adaptability of EstD9 under extreme conditions via in silico approaches. Circular dichroism revealed that EstD9 generated new β-sheets at 80 °C, making the core of the hydrolase fold more stable. Interestingly, the profiles of molecular dynamics simulation showed the lowest scores of radius of gyration and solvent accessible surface area (SASA) at 80 °C. Three loops were responsible for protecting the catalytic site, which resided at the interface between the large and cap domains. To further investigate the structural adaptation in extreme conditions, the intramolecular interactions of the native structure were investigated. EstD9 revealed 18 hydrogen bond networks, 7 salt bridges, and 9 hydrophobic clusters, which is higher than the previously reported thermostable Est30. Collectively, the analysis indicates that intramolecular interactions and structural dynamics play distinct roles in preserving the overall EstD9 structure at elevated temperatures. This work is relevant to both fundamental and applied research involving protein engineering of industrial thermostable enzymes.